Designing a Human-Centered Smart Counter for Transjakarta Using the House of Quality to Improve Service Inclusivity - Nova Pangastuti; Olivia Oktariska Timbayo; Restu Pinasthika (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Jakarta's increasing vehicle usage has exacerbated air pollution, and as a result, the initiative to advance sustainable urban mobility and a target to achieve Net Zero Emissions by 2050. Nevertheless, public satisfaction with Transjakarta remains low due to inconsistent service quality and no real-time information for riders. This study puts forward the SmartCounter, a smart passenger-counting system developed by a Human-Centered Design (HCD) process with support from the SERVQUAL approach and House of Quality (HoQ) analysis. The research employs a mixed-method methodology using gap analysis, semi-structured interviews, and focus group discussions to comprehensively gather and convert user requirements into technical specifications. Critical parameters that are elicited from SERVQUAL then propel the Voice of Customer and subsequently get mapped to ranked technical needs with the help of the HoQ. SmartCounter utilizes cutting-edge sensing technology (Time-of-Flight or AI-integrated cameras) with onboard edge computing to enable automatic, real-time, and privacy-respecting passenger counting. The HoQ study prioritized three main technical imperatives: sensor accuracy (score 123), casing robustness (score 111), and real-time transmission (score 109). Other aspects include embedded processors (score 103), display units and operator dashboards (scores 84), and power systems (score 71). Overall, the SmartCounter actively addresses both passenger and operational needs, advancing Jakarta's goals towards a more sustainable, efficient, and inclusive urban transport system for Net Zero Emissions 2050.